Elucidating Electrochemical Properties Of Suitable Polymer Coated On Carbon Electrode To Detect Heavy Metals - Zaharum, Nurul Hanisarina (Universiti Sains Malaysia, 2022)
Environmental pollution by heavy metals (HMs) have gained global attention due to high toxicity, poisonous and non-biodegradable in nature even at low concentration, which poses serious threats to human health and environment. Therefore, the development of detection methods that is simple, highly sensitive and good selectivity in detection of HMs is crucial. Screen printed electrode (SPCE) is widely used as working electrode (WE) in electrochemical sensor as it offers several advantages such as portability, excellent sensitivity, selectivity and on-site analysis with short detection time. Modification of the surface WE by using polymer also gained attention in development of electrochemical sensor in detection of HMs due to unique properties such as anti-fouling properties by forming a protective surface, high stability and fast electron transfer kinetics. From this work there are several goals in in Sustainable Development Goals (SDGs) is achieved which are Goal 6 (clean water and sanitation), Goal 7 (affordable and clean energy) and Goal 9 (industry, innovation and infrastructure).In this thesis, the electrochemical properties of suitable polymer coated on SPCE in detection of HM such as lead (II) ions (Pb2+) was studied. There are three types polymer were used for modification of SPCE which are chitosan, nylon 6 and cellulose acetate by using drop coating method. Voltammetry method such as cyclic voltammetry (CV) and stripping voltammetry (SV) were used in determination of current response and detection of Pb2+ ions due to its high precision and sensitivity. The physical and chemical properties of modified SPCE (M – SPCE) was5 characterized by using light microscope and fourier transform infrared spectroscopy (FTIR). It observed that there are significant changes of the structure and functional groups of the M – SPCEs for all polymers. The conductivity of M – SPCE was observed by using CV method. It was observed that the modified chitosan on SPCE (CTS/SPCE) showed the best conductivity compared to modified nylon 6 on SPCE (Nylon 6/SPCE) and modified cellulose acetate on SPCE (CA/SPCE). The thickness of polymer film also studied by manipulating the thickness film which are 20, 40 and 60 μL to study the conductivity by using CV method. The thickness of polymer film of 20 μL seems to best conditions to coating as the peak of current showed the highest followed by 40 and 60 μL. The sensitivity of detection of Pb2+ ions was studied by manipulating the concentration of coating polymers (1, 3 and 5 wt.%) and concentration of Pb2+ ions in analyte (0.1 to 1.9 ppm) by using square wave stripping voltammetry (SWSV). At 1 and 3 wt.% concentration of coating polymer, modified CTS/SPCE showed the best sensitivity with low limit of detection (LOD) value of 0.0699 and 0.01817 ppm, respectively. Meanwhile, modified CA/SPCE showed the best sensitivity with LOD value of 0.06598 ppm and modified Nylon 6/SPCE showed the best sensitivity with LOD value of 0.09775 ppm at 5 wt.% concentration of coating polymer. With increasing the concentration of coating polymers, the performance of modified Nylon 6/SPCE and CA/SPCE also improved in detection of Pb2+ ions. Thus, this indicated that the concentration of coating polymers affected the performance of electrochemical sensor. However, nylon 6 and cellulose acetate is not suitable to be used for modification of SPCE as it showed low sensitivity compared to bare SPCE. Overall, the modified CTS/SPCE showed the best electrochemical properties with high sensitivity and suitable to be used in development of SPCE in detection of Pb2+ ions.